Entwicklung eines Argumentationskompetenzmodells für den Geographieunterricht - Budke, Alexandra; Schiefele, Ulrich; Uhlenwinkel, Anke (Zeitschrift für Geographiedidaktik (ZGD), 2010)
In a postmodern society being able to discuss is one of the most important competences. Therefore, the National Standards for Geography explicitly formulate the goal of students’ achieving communication skills. In order to accomplish this, it is proposed to develop a competence model of argumentation skills. Arguments usually have two sides: the structure of the argument which is field-invariant and the content of the argument which is field-dependent. A suitable basis for the field-invariant aspects of arguments are the Common European Framework of Reference for languages, which proposes a model for communication skills and the influential model of the structure of an argument offered by Toulmin.
Keywords: argumentation skills, competences, geography lessons